Pengaruh Kepemimpinan dan Lingkungan Kerja Terhadap Motivasi Kerja Karyawan pada Hotel Four Points By Sheraton Jakarta, Thamrin - Radja Daffa Razoqi; Dewi Susita; Christian Wiradendi Wolor (Indonesia Economic Journal, 2025)
This study aims to analyze the influence of leadership and work environment on employee work motivation at the Four Points by Sheraton Hotel Jakarta, Thamrin. The research method used is quantitative with an explanatory approach. The number of respondents was 50 employees, with a saturated sampling technique. Data analysis was conducted using multiple linear regression. The results of the study indicate that leadership has a significant positive effect on work motivation, while the work environment has a significant negative effect. This finding indicates that the current work environment can reduce motivation, so it is necessary to evaluate the physical and non-physical aspects that shape the work atmosphere. This study provides important implications for management in increasing productivity through improving a more conducive work environment